Porous hydrogel constructs based on methacrylated gelatin/polyethylene oxide for corneal stromal regeneration. (August 2022) - Lu, Xiaoting; Song, Wenjing; Sun, Xiaomin; Liu, Jia; Huang, Yongrui; Shen, Jingjie; Liu, Sa; Han, Qianqian; Ren, Li
Abstract: The lack of donor sources for corneal transplantation leads to the development of alternative materials for corneal regeneration and repair. As the stroma occupies the thickest layer of the cornea, biomimetic corneal stromal constructs were widely observed by tissue engineering. In this study, a light-curing porous hydrogel based on the two-phase aqueous emulsion was prepared to induce the regeneration of corneal stroma. Methacrylated gelatin (GelMA) solution containing photoinitiator was mixed with aqueous polyethylene oxide (PEO) solution to form an immiscible two-phase emulsion. We characterized physical and chemical properties, containing the pore size, mechanical properties, degradation properties, and swelling properties, to choose the preparation process of the porous hydrogel. The in vitro studies performed in this study suggested that the porous hydrogels had good biocompatibility and the specific matrix secreted by corneal stromal cells gradually increased, so the porous hydrogels promoted the secretion of extracellular matrix. The hydrogels were inserted in a mid-stromal pocket created by minor surgery to confirm their histocompatibility and application in corneal regeneration and repair. Graphical Abstract: ga1 Highlights: The light-curing porous hydrogel was based on the two-phase aqueous emulsion to prepare corneal stromal construct. The corneal stromal cells within the porous hydrogels secreted the specific matrix. The porous hydrogels encapsulated with corneal stromal cells induce the regeneration of the corneal stroma in vivo .